In vitro mimicry of in vivo KPC mutations by ceftazidime-avibactam: phenotypes, mechanisms, genetic structure and kinetics of enzymatic hydrolysis - Siquan Shen; Chengkang Tang; Weiwei Yang; Li Ding; Renru Han; Qingyu Shi; Yan Guo; Dandan Yin; Fupin Hu (Emerging Microbes and Infections)
Ceftazidime-avibactam (CZA) is employed for the treatment of infections caused by Klebsiella pneumoniae carbapenemase-producing K. pneumoniae (KPC-KP). Resistance to CZA is frequently linked to point mutations in the blaKPC. We conducted in vitro simulations of in vivo blaKPC mutations using CZA. Four pre-therapy KPC-KP isolates (K1, K2, K3, and K4) were evaluated, all initially exhibited susceptibility to CZA and produced KPC-2. The crucial distinction was that following CZA treatment, the blaKPC-2 mutated in K1, K2, and K3, rendering them resistant to CZA, while K4 achieved microbiological clearance, and blaKPC-2 remained unaltered. The induction assay identified various blaKPC-2 variants, including blaKPC-25, blaKPC-127, blaKPC-100, blaKPC-128, blaKPC-137, blaKPC-138, blaKPC-144 and blaKPC-180. Our findings suggest that the resistance of KPC-KP to CZA primarily results from the emergence of KPC variants, complemented by increased blaKPC expression. A close correlation exists between avibactam concentration and the rate of increased CZA minimum Inhibitory concentration, as well as blaKPC mutation. Inadequate avibactam concentration is more likely to induce resistance in strains against CZA, there is also a higher likelihood of mutation in the blaKPC-2 and the optimal avibactam ratio remains to be determined. Simultaneously, we selected a blaKPC-33-producing K. pneumoniae strain (mutated from blaKPC-2) and induced it with imipenem and meropenem, respectively. The blaKPC-2 was detected during the process, indicating that the mutation is reversible. Clinical use of carbapenems to treat KPC variant strains increases the risk of infection, as the gene can mutate back to blaKPC-2, rendering the strain even more cross-resistant to carbapenems and CZA.